The Political Image of Left-wing Leaders in Poland: How Young Voters Evaluate the Politicians from Different “Political Generations” - Marmola, Maciej; Darmoń, Krzysztof (Political Preferences, 2022)
In recent decades political activity has become more and more personalized. Thus, to achieve political success, it is necessary to have a recognizable and popular party leader. Polish left-wing parties have adopted a different strategy. Instead of betting on one leader, they promote “three tenors” from different political generations (Robert Biedroń, Włodzimierz Czarzasty, and Adrian Zandberg). The aim of our study (N=379) is to diagnose how voters perceive the political images of these left-wing leaders and what feelings they have towards them. We confirm the findings from other studies suggesting the effect of political preferences and ideological orientation on the perception of political image and emotional attitudes to party leaders.